ASSESSMENT OF THE TREATMENT RESULTS BY SURFACTANT FOR ENDOTHELIAL LUNG DISEASE IN PREMATURE INFANTS AT HUNG YEN OBSTETRICS AND CHILDREN'S HOSPITAL IN 2020-2021 (Vietnam Journal of Community Medicine, 2022)
Objectives: Describe clinical and paraclinical characteristics of respiratory distress syndrome inpremature infants with endothelial disease and evaluate the results of treatment with Surfactanttechnique at Hung Yen Obstetrics and Children's Hospital in 2020 - 2021.Subjects-methods: Design of a cross-sectional descriptive study comparing before and afterSurfactant treatment. All premature infants with diagnosis confirmed treated with surfactant(Curosurf). Administer curosurf 116mg/1 vial single dose for premature infants at a dose of 100-160 mg/kg. Choose a convenient sample size for preterm infants who are eligible for the study.Results: 98% of children breath well. Amniotic fluid in 94.9%; respiratory failure early in the firsthour (Silverman score >6). Exhausted breathing; moaning 82.4%, retraction 79.4%, SpO2 below90% was 91.8% and 8.2% of children had hypothermia. There is grade 3 X-ray damage. Heartrate, breathing rate, and FiO2 after 6 hours of treatment all decreased statistically significantly(p
Keywords: Premature infant; respiratory failure; Surfactant.